The Scorpion King [videorecording (DVD)] - Sommers, Stephen; Johnson, Dwayne, 1972-; Brand, Steven, 1969-; Hu, Kelly, 1968- (Franchise collection., 2002)
Mighty Memnon rules over nearly all the known world, who defeats his enemies in battle with the help of a beautiful sorceress. "Free tribes" form a fragile alliance to fight Memnon, and hire a trio of assassins to kill the sorceress and thus remove Memnon's advantage. The assassins are betrayed by the son of one of the tribal leaders, and Mathayus finds himself unable to kill Cassandra. Mathayus abducts the sorceress, who explains that Memnon was holding her against her will. Mathayus then uses his newfound sense of justice to convince the surviving tribal leaders to join forces again to defeat Memnon.